Effect of Endophytic Bacterium Inoculation on Sprouts and Microgreens Growth of Common Buckwheat (Fagopyrum essculentum) Species - Briatia, Xoxiong; Khanongnuch, Chartchai; Ho Park, Cheol (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
This paper describes the potential use of endophytic bacterium strains (Herbaspirillum rubrisubalbicans) to stimulate seed germination in both common and tartary buckwheat. The experiment was conducted in a growth chamber under dark conditions and temperature maintained at 20, 25 and 30ºC, for 7 days. Thirty seeds for each treatment with three replications in completely randomized design (CRD) were used. The results showed that seeds inoculated with endophytic bacterium induced increases in seed germination parameters, in some cases achieving increases seed germination vigor rate up to 90-95% and total seed germination rate up to 95-100%, particular when the seeds inoculated with 10 and 20% (v/v) concentrations and treatment durations for 4 to 8 h, which showed higher than other germinated conditions. However, increased inoculants concentration and treatment durations up to 40% (v/v) and 12 h may be decreased seed germination parameters rapidly compared to others. In present study, the optimum temperature conditions for both common and tartary buckwheat seed germination test would be ranged from 20 to 30ºC, and between the species found that seed inoculation with endophytic bacterium showed higher seed germination parameter in common buckwheat than tartary buckwheat under each tested conditions. Finally, our conclusion that seed application with Herbaspirilum rubrisubalbicans strain in a proper concentrations and durations (10 to 20% (v/v), for 4 to 8 hours) may be recommended as a most effective treatment to promote seed germinations, seedling vigor and seedling establishment in both common and tartary buckwheat species.